Pemphigus Vulgaris in Pregnancy: A case report - Trisepti Utami Desak Nyoman; Nyoman Suryawati; Herman Saputra; Nevristia Pratama (Faculty of Medicine, Universitas Airlangga, 2026)
Background: Pemphigus vulgaris (PV) is a common form of pemphigus but is rarely triggered by pregnancy. PV in pregnancy can increase the risk of neonatal pemphigus, premature birth, and fetal death. Case: Female, 38 years old, third pregnancy, 5th-week pregnancy, complaints of blisters on the skin since five days. The complaint started with sores in the oral cavity and progressed to blisters that broke easily on the skin. The dermatological status in the anterior and posterior thoracoabdominal regions revealed multiple flaccid bullae, 0.8-2 cm, some with crust-covered erosion, a positive Nikolsky sign, and a mousy odor. The Tzank test revealed acantholytic cells and histopathology appropriate for PV. The patient was diagnosed with PV in pregnancy and treated with 40 mg methylprednisolone and 0.9% NaCl compress on erosion, crusting lesions, and paraffin tulle on erosion. She got improved. Discussion: While systemic steroids are the recommended treatment for PV in pregnancy, this therapy carries a risk of causing oral clefts, low birth weight, premature birth, preeclampsia, and gestational diabetes mellitus (DM). Our patient showed no signs of preeclampsia or gestational diabetes, had a normal delivery, and gave birth to a premature, vigorous baby with a low birth weight based on gestational age.